Pengaruh Corporate Culture, Motivasi Karyawan, Dan Inovasi Organisasi Terhadap Praktik Kepemimpinan Transformasional di PT KAI Daop 6 Yogyakarta - Adi Prasetyo; Surya Darmawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of corporate culture, employee motivation, and organizational innovation on transformational leadership practices at PT KAI DAOP 6 Yogyakarta. This study uses a quantitative approach with a survey method. The sample was determined using a purposive sampling technique, and the questionnaire was compiled using a five-point Likert scale. A total of 95 respondents who were permanent employees of PT KAI DAOP 6 Yogyakarta with a minimum work period of one year were involved in this study. The research instrument was a closed questionnaire, and the analysis technique used was multiple linear regression. The results of the analysis showed that, both partially and simultaneously, corporate culture, employee motivation, and organizational innovation had a positive and significant effect on transformational leadership practices. This study is expected to provide practical implications for the development of leadership strategies and human resource management in public transportation organizations.